Evaluating an interprofessional disease state and medication management review model. Issue 2 (March 2014) - Hoti, Kreshnik; Forman, Dawn; Hughes, Jeffery
Abstract There is lack of literature data reporting an incorporation of medication management reviews in students' interprofessional education (IPE) and practice programs in aged care settings. This pilot study reports how an interprofessional disease state and medication management review program (DSMMR) was established in a residential aged care facility in Perth, Western Australia. Students from the professions of nursing, pharmacy and physiotherapy focused on a wellness check in the areas of cognition, falls and continence while integrating a medication management review. Students' attitudes were explored using a pre- and post-placement questionnaire. Students indicated positive experience with the IPE DSMMR program which also resulted in their positive attitudinal shift towards IPE and practice. These findings indicated that aged care can be a suitable setting for student interprofessional programs focusing on DSMMR.